Eco-friendly pomegranate production: Balancing energy consumption and environmental impact - Amir Azizpanah; Mohammad Salavrzi Zadeh; Alaa Kamil Abed; Morteza Taki (PLoS ONE, 2025)
Pomegranate production in Siab (Lorestan), Iran, faces significant challenges related to high energy consumption and environmental degradation, particularly due to inefficient use of agricultural inputs such as fertilizers, water and machinery. These inefficiencies contribute to increased greenhouse gas emissions and higher production costs, making optimization efforts essential for sustainable development. This study investigated the optimization of energy consumption and the reduction of environmental impacts in pomegranate production using a combination of Data Envelopment Analysis (DEA) and Life Cycle Assessment (LCA). Data were collected through interviews with farmers and agricultural experts in the region, supported by structured questionnaires. The research evaluated several energy indicators, including an energy ratio of 2.14, which indicates that every unit of energy input yields more than double in output—comparable to other fruit crops like apple or citrus, which typically range between 1.5 and 3.0. Energy productivity was found to be 1.12 kgMJ-1, meaning 1.12 kilograms of pomegranate are produced per megajoule of energy consumed, while specific energy was calculated at 0.89 MJkg ⁻ ¹, showing relatively efficient energy use compared to similar horticultural crops. Net energy gain was 17,142.33 MJha ⁻ ¹, with total energy consumption at 15,211.04 MJha ⁻ ¹ and an energy output of 32,353.38 MJha ⁻ ¹. Economic analysis revealed a gross value of 9,081.64 USDha ⁻ ¹, fixed costs of 204.44 USDha ⁻ ¹, and gross revenue of 8,059.42 USDha ⁻ ¹, resulting in a benefit-to-cost ratio of 0.83. LCA results showed that optimized practices significantly reduced environmental impacts across most of the 15 intermediate environmental indicators analyzed. For instance, global warming potential was reduced from 40.563 kg CO₂ eq per ton of pomegranate under conventional methods to 35.975 kg CO₂ eq with optimized practices. DEA under the Variable Returns to Scale (VRS) model revealed that 66.68% of the surveyed orchards operated at 100% technical efficiency. The average technical efficiency across all units was estimated at 98.96%. The remaining 33.32% of orchards were identified as technically inefficient. Scale efficiency averaged at 99.39%, suggesting that most farms operate near optimal size.